KOMUNIKASI INTERPERSONAL ANTARA BIDAN DAN PASIEN PADA PRAKTEK BIDAN MANDIRI - Priyantoko, Bagas; Kartinawati, Erwin; ., Musta’an (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2016)
The family planning program in the Klumpit village, Gebog, Kudus already going well. But people still have a low level of awareness of the decision making use contraceptives to be chosen because of several limitations. For the achievement of understanding the use of birth control in patients, then the communication is necessary for a midwife. Effectiveness of a communicator can be evaluated in terms of the extent to which these goals are achieved, one of them with therapeutic communication.This research is a qualitative description, which is used in data collection techniques nonparticipant observation, in-depth interviews, and literature review. Informants were selected based on purposive sampling. Data analysis techniques used in this study is an interactive model as proposed by Miles and Huberman. The results showed that applied therapeutic communication BPM Hj.Darini, S.SiT consists of four phases / stages, namely the pre interactions, the action phase, the phase of evaluation, and documentation phases. In doing therapeutic communication with patients, midwives use these techniques and certain attitudes. The association between the midwife with patients in BPM Hj.Darini, S.SiT are important in therapeutic communication. Through building relationships and patient midwife who built up well, midwife and patient work together to achieve goals. The purpose of therapeutic communication include: assisting patients in clarifying and reducing the burden of feelings and thoughts, and can take effective action for the patient.